ANALYSIS OF PATIENT SATISFACTION WITH THE QUALITY OF HEALTH SERVICES AT NALA HUSADA DENTAL HOSPITAL (RSGM), HANG TUAH UNIVERSITY, SURABAYA - Budi Priyono (JOURNAL ASRO, 2021)
RSGM Nala Husada Dental Hospital, Hang Tuah University, Surabaya is a center for service, development of science, dental and maritime technology as well as being the main teaching hospital for the UHT Faculty of Dentistry in order to improve people's oral and dental health. Supported by doctors, specialist dentists, pharmacists, medics, administrative personnel and adequate dental technology, it also functions to carry out dental and oral health services that prioritize treatment and patient recovery activities carried out in an integrated manner with efforts to improve and prevent as well as carry out referral efforts. Although service facilities are available Nala Husada Hospital, Hang Tuah University, Surabaya quite complete, but because of the many existing health institutions, it is very necessary to conduct research on the level of satisfaction of Nala Husada Hospital, Hang Tuah University, Surabaya. This study aims to provide input for parties Nala Husada Hospital, Hang Tuah University, Surabaya how the level of patient satisfaction with the quality of health services at Nala Husada Hospital, then what types of services need to be improved and instruments that can be used by the parties will be provided Nala Husada Hospital, to evaluate the quality of health services at Nala Husada Hospital, Hang Tuah University, Surabaya every year. Keywords: Patient satisfaction, quality of dental and oral health services, RSGM Nala Husada